How well do patient education materials for Clostridium difficile infection score? A systematic evaluation - Zellmer, Caroline; Zimdars, Peggy; Parker, Sarah; Safdar, Nasia (International Journal of Infection Control, 2015)
Patient education and engagement is key to prevention of Clostridium difficile Infection (CDI). The suitability of accessible patient education materials on CDI is uncertain. We undertook a systematic assessment of available materials for patient education on CDI using a certified evaluation tool, the Patient Education Materials Assessment Tool (PEMAT). We found that available materials received low marks on the PEMAT.